"Bad girls" or vulnerable girls? How do we see girls in special education programmes? - Doležalová, Pavla (e-Pedagogium, 2019)
The paper addresses the vulnerability of adolescent girls in preventive and therapeutic programmes of special education. At first, adolescence is defined in terms of vulnerability and the concept of vulnerability is brought into closer focus. There are also some differences in the vulnerability of girls and boys. The study focuses on selected areas of vulnerability of adolescent girls and adolescent mothers, such as risky behaviours and stigmatization. Subsequently, the article presents areas of risk and protective factors. Attention is also paid to the main vulnerability indicators of adolescent girls. Possibilities of prevention, early intervention, psychotherapy and treatment are outlined by the schema. The paper may be appropriate for good practice and research.
Keywords: Key words: vulnerability; adolescent girls; vulnerability indicators; risk and protection factors.